1ISG-030 Biologics utilisation and its efficiency through a hospital pharmacy centralised management system. (March 2019) - Feio, J; Poitier, S; Machado, F; Vandewalle, B; Andreozzi, V; Félix, J
Abstract : Background: In October 2017 our hospital implemented a new policy for biologics' utilisation. The pharmaceutical services were responsible for the management and control of the new policy, creating the Fully Integrated Biosimilars utilisation management System (FIBS). Purpose: This research aims to provide an efficiency assessment of FIBS. Material and methods: The new policy was coincident with the introduction of biosimilars in the market and so no control group was available. In this context the FIBS system efficiency was defined as the ratio between the observed and optimal (simulated) biosimilars utilisation levels. Optimal biosimilars utilisation was estimated by mapping the FIBS process, from prescription to dispensing of biologics. The step-by-step process, including timelines and inter-dependencies between stakeholders were modelled using the Anylogic software, to simulate a counterfactual optimal level of biosimilars utilisation over time for all patients on infliximab, etanercept and rituximab between October 2017 and September 2018 (cut-off date). FIBS relies on acquisition, prescription and dispensing of biologics by international non-proprietary name and recommends: for naïve patients, the prescription and dispensing of the most economically accessible biologic (brand or biosimilar) is mandatory; and maintaining the same biologic brand in patients for a period of no less than 12 months. After this period, conditions exist to transition to the economically most accessible biologic available. Exceptions require a clinical justification on a patient-by-patient basis by prescribing physicians. Exceptions need to be validated by the Hospital Pharmacy, Hospital Medicines and Therapeutic Committee and Hospital Board. Results: A total of 543 patients were analysed since October 2017. The level of FIBS system efficiency increased very rapidly in this short time: 50% (2 months) and 80% (4 months). System efficiency of FIBS has been increasing steadily since then, reaching levels above 85% in September 2018. This means that 85% of patients eligible (optimal) for biosimilar utilisation were on biosimilar therapy 11 months after policy initiation and FIBS implementation. Conclusion: The Fully Integrated Biosimilars utilisation management System demonstrates high levels of system efficiency in the utilisation of biologic therapy at hospital level, less than one year after its implementation. References and/or acknowledgements: No conflict of interest.